PENGARUH MOBILISASI DINI PADA IBU POST PARTUM TERHADAP KECEPATAN PENYEMBUHAN LUKA PERINEUM DI PUSKESMAS KASSI-KASSI MAKASSAR - Nurhikmah; Rusli Taher (Stikes Graha Edukasi Makassar, 2020)
Objective: The puerperium is the time that begins after the placenta is born and is about 6 weeks. However, the entire contents returned to normal as before pregnancy occurred within approximately 3 months. Early mobilization in post partum mothers depends on the condition of the patient if the patient is delivering normally, it can be done after 2-4 hours after delivery. Method: The study was conducted in November 2019 at the Kassi-Kassi Makassar Public Health Center. This type of research is quantitative Quasy Experiment. The population in this study were all postpartum mothers visiting the Kassi-Kassi Makassar Public Health Center, as many as 16 people were treated and 16 people were not treated. Results: The results showed that 19 people (59.4%) did early mobilization and 13 people (40.6%) did not mobilize early. The results showed that there were 21 people (65.6%) perineum wound healing and 11 people (34.4%) who were slow. The results showed that there was an influence of early mobilization on the speed of perineal wound healing obtained p value = 0.022 <? 0.05. Suggestion: It is expected that mothers do early mobilization to understand techniques and how to do early mobilization movements so that mothers can do it themselves without the help of health workers